Organic Acids and Carbon Profiles by Bifidobacteria Pseudocatenulatum G4 During Cultivation in Low Concentrations of Milk Medium - Khalil, Khalilah Abdul; Musa, Maslinda; Ahmad, Siti Aqlima; Mustafa, Shuhaimi (The Asia Journal of Applied Microbiology, 2017)
Growth characteristics of Bifidobaceria pseudocatenulatum G4 in low concentration milk medium were studied. During cultivation process, profiles of cell growth, pH changes, organic acids and sugar profile were monitored. A finding showed that final cell concentration (cfumL-1) obtained in 2 and 4% (w/v) milk concentration was two times lower than in comparative media. However, 6% (w/v) skim milk gave a promising media for B. pseudocatenulatum G4 growth. Organic acids production (acetic, lactic, formic and citric acid) by strains was detected in all milk medium concentrations and similar profile were observed. Except for formic acid which actively produced in 2 and 4% (w/v) milk concentration. The accumulation of formic acids was believed due to carbon limitation. As for sugar profile, co-metabolized galactose and glucose were observed in 2, 4 and 6% (w/v) skim milk concentration. Meanwhile high carbon remains occurred in 8 and 10% (w/v) milk concentrations after cultivation period. Among all concentrations, milk with 6% (w/v) concentration showed better support for cells growth without formic acid presence and low carbon remains at the end of cultivation period.